Widespread heavy damage of capillary endothelial cells in the pathogenesis of sarcoidosis – Evidence by monoclonal von Willebrand factor immunohistochemistry in the bronchus and lung of patients with sarcoidosis - Mochizuki, Ichiro; Kubo, Keisi; Hond, Takayuki (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
We have observed that electron microscopically there were many damages of the plasma membrane of the bronchial and lung capillary endothelial cells in sarcoidosis and at the same time, platelets adhesion and eosinophil attached to the capillary vessels. And characteristically, the capillary endothelial cells showed appearance of the lipid droplets including saturated and unsaturated fatty acids in the cytoplasm and capillary lumina in all cases. For elucidation of the functions in the capillary endothelial cells, we performed the histochemical study of monoclonal antibody for von Willebrand factor (vWf) antigen by the ABC method on the 22 bronchial and lung biopsied cases and 15 control subjects. The vWf showed a strong reaction in wide range with exsudation towards outside and occlusion or dilatation in the capillary walls and the area showing alveolitis disclosed also strong reactivity with exsudation. Dilated or occluded capillaries were observed and finally they disappeared in the tissue. These widespread capillary’s hyperreactivity were observable in the remote area from granuloma, and the capillaries in the matured granulomas were found significantly reduced in immunostained of vWf. These wide distributed changes of the capillary endothelial cells involving exsudation and other various grade of damage suggest the endothelial pertubation or damage may already occur before granuloma formation and we propose that sarcoidosis is the capillary disease occurred in the plasma membrane of the endothelial cells as a formal pathogenesis. From a standpoint of lipid biology about the endothelial cells, molecular components on the surface of the endothelium and the bacteria’s membrane lipoglycan were discussed.